Exploring the School Heads Working Condition in Supporting Communities of Practice (CoP) and Technical Assistance (TA) to Teachers: A Multiple Case Study - Catedral, Rey R.; Datulayta, Rene G.; Lawan, Pilot B.; Lumbuan, Jenevieve D.; Carbon, Rechiel B. (Future Science / FSH-PH Publications, 2023)
This study explored the school heads’ working conditions in supporting Communities of Practice and Technical Assistance to teachers as vehicles to address problems in the teaching and learning processes and promote learning and collaboration within organizations. A qualitative research design employing multiple case study methods was utilized. The study included one (1) Principal-in-Charge (PIC), three (3) school heads, and three (3) master teacher positions. A total of seven (7) participants participated in this study. Moreover, the study employed semi-structured interview guide questions. The data were analyzed using Colizzi's thematic analysis. The results showed that the working conditions supporting the communities of practice and technical assistance to teachers are classroom observation, learning action cell, In-Service Training (InSeT), and conference and urgency. The following working conditions may affect or influence school heads and master teachers in supporting communities of practice and technical assistance to teachers: intellectance (openness to new experiences), communication channels, schedules, lack of leadership, and knowledge of technical assistance providers. Participants experienced challenges, motivations, fulfillment, and positivity in implementing CoPs and TAs. The following themes were coded on the influence of experiences on communities of practice and technical assistance to teachers: positivity, flexibility, thriving, social support and interaction, and positivity. The openness to new experiences, such as a sense of curiosity, open-mindedness, and acceptance of novel experiences, is needed for CoPs and TAs to prosper in school. Communication channels should be clear and appropriate to their audience, allow deeper conversations, and exchange ideas, thoughts, opinions, knowledge, and data in CoP and TA should be understood with clarity and purpose. School leaders must be empowered with managerial and leadership skills to support and influence communities of practice and technical assistance to teachers.